Implementation of Internet of Things (IoT) in Information System - Judijanto, Loso; Vandika, Arnes Yuli; Priyana, Yana (Westscience Press, 2024)
This study employs bibliometric analysis to map the network of research collaborations within a specific academic field, identifying key contributors and the structure of their interconnections. By analyzing data from prominent academic databases, the study visualizes clusters of authors and assesses their influence based on publication and citation metrics. The findings offer strategic insights into the core research communities, highlighting central authors and potential areas for collaboration. Practical implications are discussed for academic institutions, research networks, and funding strategies, emphasizing how these entities can utilize the analysis to enhance research output and innovation. Limitations of the study include potential database biases and a focus on quantitative measures, which may not fully capture the dynamic and qualitative aspects of individual contributions. Despite these challenges, the bibliometric analysis provides valuable guidance for strategic decision-making in research and academic communities.